A Two-Stage Regularization Method for Variable Selection and Forecasting in High-Order Interaction Model. (11th November 2018) - Dong, Yao; Jiang, He
Abstract : Forecasting models with high-order interaction has become popular in many applications since researchers gradually notice that an additive linear model is not adequate for accurate forecasting. However, the excessive number of variables with low sample size in the model poses critically challenges to predication accuracy. To enhance the forecasting accuracy and training speed simultaneously, an interpretable model is essential in knowledge recovery. To deal with ultra-high dimensionality, this paper investigates and studies a two-stage procedure to demand sparsity within high-order interaction model. In each stage, square root hard ridge (SRHR) method is applied to discover the relevant variables. The application of square root loss function facilitates the parameter tuning work. On the other hand, hard ridge penalty function is able to handle both the high multicollinearity and selection inconsistency. The real data experiments reveal the superior performances to other comparing approaches.